Kashmir as a Center of Global Conflict: Historical, Political, and Diplomatic Perspectives - Akram, Ahmad Syauqi; Fitriyah, Aidatul (Indonesian Scientific Publication, 2024)
Kashmir, a strategic region in the Himalayas, has long been a centre of historical, cultural, and political significance. Its geopolitical complexity stems from its contested status between India and Pakistan, with additional international involvement shaping the ongoing conflict. This research aims to provide a comprehensive analysis of the Kashmir conflict by examining its historical background, key political events, and the broader implications of territorial disputes. The study employs a literature review approach to identify significant themes, including the historical evolution of Kashmir, the impact of the 1947 partition and Maharaja Hari Singh's accession to India, as well as contemporary challenges such as human rights violations and international diplomatic efforts. The findings reveal that the conflict is deeply rooted in historical grievances, political manoeuvring, and competing nationalistic ideologies. The study concludes that achieving a resolution requires sustained diplomatic efforts and a commitment to addressing the socio-political concerns of the Kashmiri people. This research contributes to the broader discourse on regional conflicts and international mediation by offering insights into the historical and political dimensions of the Kashmir dispute.